Diffuse thoracic and peritoneal papillary mesothelioma in an adult cow: case report - Toledo, Frank A. O.; Gonçalves, Aline D. B. B.; Toscano, Mariela F.; Fazzano, Eduardo H.; Fernandes, Fernando V.; Cassali, Geovanni D.; Rozza, Daniela B. (Brazilian Journal of Veterinary Pathology, 2018)
Mesothelioma is a rare tumor of mesothelium and usually spread by implantation in the same cavity it arises. Regarding bovine mesotheliomas, the abdominal cavity is the most affected site. This article describes a case of diffuse papillary mesothelioma within both thoracic and abdominal cavity with nodal metastasis in an adult cow - based on cytology, histopathology, and immunohistochemical analysis. A 7-years-old cow, Nelore breed (Brazilian beef cattle), with clinical signs of tachypnea, abdominal distention, and positive jugular venous pulse was slaughtered and necropsied due to persistent weight loss. The main gross findings were several verrucous and yellowish nodules spread on pericardium, pleura, and peritoneum. Mediastinal lymph nodes were enlarged and hemorrhagic with multiples yellowish spots on cut surface. The diagnoses of diffuse mesothelioma with nodal metastasis was established and ratified by the microscopic analysis. Immunohistochemical results had strong positivity for cytokeratin and the Ki-67 showed proliferative index of 28%. Vimentin was positive only in the cells of fibrous tissue. In this case, the initial site of the mesothelioma was not recognized. Although it is a post-mortem study, cytology may be very helpful in vivo investigation. Equally important, is the IHC to better comprehend this tumor and its behavior.